Percutaneous surgery in the treatment of Haglund syndrome: a systematic review - Gomes, Marília; Monteiro, Gabriel; Arteiro Neto, José (Journal of the Foot & Ankle, 2020)
Objective: The present study aimed to verify the state of the art of minimally invasive percutaneous surgical treatment for Haglund syndrome. Methods: This systematic review of the literature was based on a bibliographic survey in the PubMed, Medline and Embase databases. The descriptors "Haglund syndrome", "Haglund", "Achilles", "Minimally invasive", "Percutaneous surgery" and "Osteotomy" were used, in addition to the filters "Randomized Controlled Trial", "Randomized Clinical Trial", "Meta-Analysis", "Systematic Reviews", "Reviews", and "Clinical Trial". Results: A total of 37 articles were included. The total number of patients with Haglund syndrome treated in the included studies was 831 and 920. The mean patient age was 46.6 years (range, 28.7 to 61) and 58% were men. A higher success rate and a lower rate of complications were reported in men, and physically active patients had better treatment results. The mean success rate for minimally invasive percutaneous procedures was 83.4% (range 66 to 100%). Overall patient satisfaction was 77.5% (range 60 to 95%) and the complication rate was 6.3% (range 0 to 23%). Conclusion: Despite a lack of studies with the recommended evidence level, minimally invasive and percutaneous surgical treatments seem to be a good option for patients with Haglund syndrome when conservative treatment fails. Level of Evidence III; Therapeutic Studies; Systematic Review of Level III Studies.